Diagnóstico ergonômico das atividades de empacotamento, carregamento e empilhamento de gelo em uma pequena empresa - Queiroz, Natália Crystina Silva de Moura (Universidade Federal Rural do Semi-Árido, 2020)
In recent years organizations have shown greater interest in adopting ergonomic tools, but small companies are not always able to follow the established standards. As for the ice factories, it is observed that the activities are mostly carried out in a way that is inadequate for the workers. The Ergonomic Analysis of Work (AET) aims to analyze the actual activity, while trying to understand the complexity that exists in the relationship between work and man. Therefore, this work aimed to perform an ergonomic diagnosis of the activities of packing, loading and stacking ice in a small company located in the city of Mossoró - RN. For this, the working conditions were evaluated, observing how these activities are performed and how they are prescribed. Based on these analyses, an SPM diagnosis was prepared. The results showed that there was discrepancy in technical, operational and environmental characteristics between the prescription of tasks and how the activities were actually performed.
Keywords: Análise da atividade; empresa de gelo;; diagnóstico SPM; ENGENHARIAS::ENGENHARIA DE PRODUCAO